Injuries from antipersonnel mines: the experience of the International Committee of the Red Cross. Issue 6816 (14th December 1991) - Coupland, R M; Korver, A
Abstract : OBJECTIVE--To describe and quantify patterns of injury from antipersonnel mines in terms of distribution of injury, drain on surgical resources, and residual disability. DESIGN--Retrospective analysis. SETTING--Two hospitals for patients injured in war. SUBJECTS--757 patients with injuries from antipersonnel mines. MAIN OUTCOME MEASURES--Distribution and number of injuries; number of blood transfusions; number of operations; disability. RESULTS--Pattern 1 injury results from standing on a buried mine. These patients usually sustain traumatic amputation of the foot or leg; they use most surgical time and blood and invariably require surgical amputation of one or both lower limbs. Pattern 2 injury is a more random collection of penetrating injuries caused by multiple fragments from a mine triggered near the victim. The lower limb is injured but there is less chance of traumatic amputation or subsequent surgical amputation. Injuries to the head, neck, chest, or abdomen are common. Pattern 3 injury results from handling a mine: the victim sustains severe upper limb injuries with associated face injuries. Eye injuries are common in all groups. CONCLUSIONS--Patients who survive standing on a buried mine have greatest disability. Non-combatants are at risk from these weapons; in developing countries their social and economic prospects after recovery from amputation are poor.